Nomograms for Predicting the Risk of SIRS and Urosepsis after Uroscopic Minimally Invasive Lithotripsy. (11th March 2022) - Wang, Can; Xu, Rufu; Zhang, Yuanning; Wu, Yingbing; Zhang, Teng; Dong, Xingyou; Zhang, Rong; Hu, Xuelian
Abstract : Objective . To analyze the potential risk factors that affect the development of urosepsis following uroscopic minimally invasive lithotripsy and to develop a nomogram that predicts the probability of postoperative urosepsis. Methods . We retrospectively analyzed the clinical data from patients that underwent percutaneous nephrolithotripsy (PCNL) or ureteroscopic lithotripsy (URL) between January 2018 and December 2019. The enrolled patients were grouped twice according to systemic inflammatory response syndrome (SIRS) and quick sequential organ failure assessment (qSOFA). After univariate and multivariate logistic regression analyses, we identified the independent predictive factors affecting the development of postoperative SIRS and urosepsis, and built the nomograms. Results . From January 2018 to December 2019, 1959 patients underwent PCNL or URL, of whom 236 patients were accorded with the inclusion criteria. Of all 236 patients, 64 (27.12%) patients developed postoperative SIRS, and 17 (7.20%) patients developed postoperative urosepsis. Multivariate logistic regression analysis showed that positive preoperative urine culture (PUC+) (OR = 2.331, P = 0.044 ), procalcitonin (PCT) (OR = 1.093, P = 0.037 ), C-reactive protein (CRP) (OR = 1.017, P < 0.001 ), and neutrophil ratio (NEUT%) (OR = 1.091, P = 0.004 ) of postoperative were independent predictors of SIRS, and PCT (OR = 1.017, P = 0.003 ) and CRP (OR = 1.080, P < 0.001 ) were independent predictors of urosepsis. Additionally, the nomograms demonstrated good accuracy in predicting SIRS and urosepsis with a C-index of 0.884 (95% CI: 0.835-0.934) and 0.941 (95% CI: 0.885-0.996), respectively. Conclusions . The nomograms achieved the prediction of SIRS and urosepsis after uroscopic minimally invasive lithotripsy. Using this model, the risk of SIRS or urosepsis for an individual patient can be determined, which facilitates early diagnosis and rational treatment.